Coordinated generation and transmission expansion planning for a power system under physical deliberate attacks. (March 2018) - Nemati, Hadi; Latify, Mohammad Amin; Yousefi, G. Reza
Highlights: To provide an MILP model for coordinating generation and transmission expansion schemes to reinforce the power system against physical deliberate attacks. To provide a scenario building procedure for physical deliberate attacks in which the annual load variations impacts on attacks and resulted scenarios are considered. To consider multiple attack scenarios in the proposed planning framework (that are weighted proportional to their effective inflicting damage on the power system) in a yearly horizon. To study the effects of various input parameters on the optimal expansion planning. Abstract: This paper proposes a static model for coordinated generation and transmission expansion planning (CGTEP). While reducing the cost of investment, operation and energy not served within the system, the model aims to mitigate the vulnerability of power system against physical deliberate attacks in the horizon of planning. Moreover, the peak load of twelve days in a year is taken as a sample of the months to well consider the impacts of load variations over a year. The physical deliberate attacks and their subsequent impacts are also assessed through scenario building procedure. To this end, each scenario in any given month is built as an attack plan targeting transmission system and accordingly they are assigned weights proportional to the consequent damage inflicted on the power system. According to the generated scenarios for physical deliberate attacks, CGTEP is modeled as a mixed integer nonlinear programming problem (MINLP), where the network operation constraints are described by DC power flow equations in different scenarios. Afterward, using some linearization methods, the planning problem is transformed to a mixed integer linear programming (MILP) problem that can be solved by conventional optimization software. Finally, the proposed model is implemented in IEEE 24-bus reliability test system (RTS) and then numerical results are yielded to assess several case studies. The effect of input parameters on the model such as the budget of expansion planning, the number of scenarios, different objective functions, the value of shed load and also different load levels are analyzed. The significance of the proposed approach in mitigating power system vulnerability is well confirmed by numerical results.